Determinan Penipuan Akuntansi yang Dimoderasi Sistem Pengendalian Internal - Uhaiba, Syafina Rahmaniyah; Maslichah, Maslichah; Sari, Arista Fauzi Kartika (Universitas Islam Malang, 2024)
Accounting fraud often occurs in various companies and organizations, this causes companies and organizations to experience large losses. This research aims to examine the determinants of accounting fraud which are moderated by the internal control system. The object of this research is the Malang City BUMN Branch Office. A total of 70 data were collected using a purposive sampling method questionnaire. This data analysis method uses two types, namely multiple regression analysis and moderated regression analysis using the SPSS application. The test results show that the variables fraud triangle, compensation system, unethical behavior without any moderating variables show that these variables have a significant positive effect on accounting fraud. The variable compliance with accounting rules and the internal control system shows that these variables have no effect on accounting fraud. Test results with the interaction of moderating variables, the internal control system moderates the influence of the fraud triangle, compensation system, and unethical behavior on accounting fraud, but the internal control system variable does not moderate the influence of compliance with accounting rules on accounting fraud.Keywords: Accounting fraud, internal control system, fraud triangle, compliance with accounting rules, compensation system, unethical behavior